Validation of the German Version of the Quality of Dying and Death Questionnaire for Health Professionals. (September 2016) - Heckel, Maria; Bussmann, Sonja; Stiel, Stephanie; Ostgathe, Christoph; Weber, Martin
Purpose: To validate the Quality of Dying and Death (QoDD) instrument for health professionals (QoDD-D-MA) and to test its feasibility in 2 German palliative care units (PCUs). Methods: The QoDD was translated from English to German and then retranslated following European Organisation for Research and Treatment of Cancer (EORTC) guidelines. Data were collected in 2 German PCUs to calculate aspects of validity and reliability. Results: Mean total score was 83.05 (range 49-100; N = 232). The QoDD-D-MA showed satisfactory psychometric properties, Cronbach α = .830; interrater reliability r = .245 ( P < .01). The QoDD-D-MA was independent of patients' demographic and clinical aspects. Some challenges occurred when applying the instrument. Conclusions: Feasibility could be improved by adapting the QoDD-D-MA to create a self-assessment version and finding a solution for items that result in many missing data. Future research should validate the QoDD-D-MA in other care settings.